2010
DOI: 10.2174/187221110789957174
|View full text |Cite
|
Sign up to set email alerts
|

Microporation Techniques for Enhanced Delivery of Therapeutic Agents

Abstract: Perhaps the greatest barrier to development of the field of transmembrane drug delivery is that only a limited number of drugs are amenable to administration by this route. The highly lipophilic nature and barrier function of the uppermost layer of the skin, the stratum corneum, for example, restricts the permeation of hydrophilic, high molecular weight and charged compounds into the systemic circulation. Other membranes in the human body can also present significant barriers to drug permeation. In order to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Dye solubility would affect the release and molecular diffusion steps of the hypothesized mechanism. Higher solubility was reported to increase drug flux across MN-treated skin since the dermis does not represent a distinct barrier to hydrophilic drugs once the SC is bypassed [45]. For instance, Stahl et al [46] demonstrated enhanced MN-driven permeation of the more hydrophilic permeants paracetamol and diclofenac compared to the lipophilic drugs ibuprofen and ketoprofen, irrespective of molecular weights.…”
Section: Discussionmentioning
confidence: 99%
“…Dye solubility would affect the release and molecular diffusion steps of the hypothesized mechanism. Higher solubility was reported to increase drug flux across MN-treated skin since the dermis does not represent a distinct barrier to hydrophilic drugs once the SC is bypassed [45]. For instance, Stahl et al [46] demonstrated enhanced MN-driven permeation of the more hydrophilic permeants paracetamol and diclofenac compared to the lipophilic drugs ibuprofen and ketoprofen, irrespective of molecular weights.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MN as a DD system is an important development as the potential to allow a wider scope of molecules to be transdermally delivered through the skin is greatly increased (Dhamech et al, 2010;Gittard et al, 2010;Milewski et al, 2010;Singh et al, 2010). The amount of drug that is delivered can also be increased.…”
Section: Increasing Permeability Of Skinmentioning
confidence: 99%
“…RF-induced thermal ablation involves a mechanism that is somewhat similar to microporation, during which resistive heating is used. Devices are equipped with an array of micro-electrodes capable of generating an electric current into the skin in the radiofrequency range (100-500 kHz), thus inducing localised heating, liquid evaporation and the removal of cells [103,104]. This results in the creation of transient aqueous microchannels across the SC, which augment the transport of water soluble entities through the skin [103].…”
Section: Radiofrequency Induced Thermal Ablation For Enhancing Transdmentioning
confidence: 99%
“…Devices are equipped with an array of micro-electrodes capable of generating an electric current into the skin in the radiofrequency range (100-500 kHz), thus inducing localised heating, liquid evaporation and the removal of cells [103,104]. This results in the creation of transient aqueous microchannels across the SC, which augment the transport of water soluble entities through the skin [103]. Transpharma Medical, which has now been acquired by Syneron Medical (Yokneam, Israel) developed the ViaDor® RF device (formerly known as ViaDerm®) (Fig.…”
Section: Radiofrequency Induced Thermal Ablation For Enhancing Transdmentioning
confidence: 99%